2017
DOI: 10.1155/2017/8196362
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hypertension in a Population of Undergraduate Students in Sierra Leone

Abstract: We report on the first survey of hypertension in undergraduates in Sierra Leone. Levels of hypertension (12%) and obesity (4%) appear low compared to the general population but given the rapid increase of both and the expectation that many graduates will enter the formal employment sector and a sedentary lifestyle, there is still cause for concern. We measured their BMI (body mass index) and used a questionnaire to investigate demographic and lifestyle choices. In agreement with most authorities, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
3
12
1
Order By: Relevance
“…[31][32][33][34] In Sierra Leone, there is widespread misinformation regarding typhoid, and in particular, widespread belief that typhoid and malaria are closely related. 35 Interestingly, people commonly conceptualise typhoid and malaria as a single disease, 'typhoid-malaria'. The belief structure linking these diseases is complex and varied.…”
Section: Key Questionsmentioning
confidence: 99%
“…[31][32][33][34] In Sierra Leone, there is widespread misinformation regarding typhoid, and in particular, widespread belief that typhoid and malaria are closely related. 35 Interestingly, people commonly conceptualise typhoid and malaria as a single disease, 'typhoid-malaria'. The belief structure linking these diseases is complex and varied.…”
Section: Key Questionsmentioning
confidence: 99%
“…While no one was having hypertension in our study sample, 4% had pre-hypertension, which marks a risk of developing hypertension in future and this could be a result of unhealthy diet and stressful lifestyle as well as familial tendency. When compared to results from other studies done in the region and the world (8,19,20,21,22,23), this prevalence is not high. According to these studies, the prevalence of hypertension among medical students and other undergraduates with ages ranging from 18 to 36 years, varied between 1.3% and 17% while the prevalence of pre-hypertension was much higher.…”
Section: Discussionmentioning
confidence: 49%
“…In fact, several studies considered the duo of age and BMI as the most significant predictor of hypertension in Nigeria 20,21,22 and elsewhere. 23,24 Firstly, the association of obesity with hypertension is important; as obesity is modifiable, it could have a strategic place in management of hypertension. Secondly, the prevalence of obesity is on the increase, and is presently assuming epidemic dimensions in several countries including Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the report of Lebbie et al where the association between family history of hypertension and blood pressure was only close to conventional level of significance ( p < 0.1 but not > 0.05). 23 A number of studies have however reported that a family history of hypertension could predict hypertension in relatives. 32 , 33 It is important to note that such self-report of history of illness or diagnosis without any objective confirmation may be prone to report or recall bias.…”
Section: Discussionmentioning
confidence: 99%